2014
DOI: 10.1002/2014jc010488
|View full text |Cite
|
Sign up to set email alerts
|

Characterizing the eddy field in the Arctic Ocean halocline

Abstract: Ice-Tethered Profilers (ITP), deployed in the Arctic Ocean between 2004 and 2013, have provided detailed temperature and salinity measurements of an assortment of halocline eddies. A total of 127 mesoscale eddies have been detected, 95% of which were anticyclones, the majority of which had anomalously cold cores. These cold-core anticyclonic eddies were observed in the Beaufort Gyre region (Canadian water eddies) and the vicinity of the Transpolar Drift Stream (Eurasian water eddies). An Arctic-wide calculatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
212
2

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 121 publications
(246 citation statements)
references
References 42 publications
32
212
2
Order By: Relevance
“…Approximately the same ratio of eddy polarization was found at mooring M1g, with 12 out of 23 eddies (or 52%) being cyclonic. This almost equal partitioning of eddies between cyclonic and 5 anticyclonic is in contrast with the findings by Woodgate et al (2001), who reported a larger amount of anticyclonic eddies compared to cyclonic eddies at the Lomonosov Ridge, as well as Zhao et al (2014), who found anticyclonic predominance for halocline eddies in the deep EB. We cannot explain this difference in ratios between cyclonic and anticyclonic eddies at the EB slope and in the deep Eurasian and Canadian basins.…”
Section: Eddy Polarization 25contrasting
confidence: 99%
“…Approximately the same ratio of eddy polarization was found at mooring M1g, with 12 out of 23 eddies (or 52%) being cyclonic. This almost equal partitioning of eddies between cyclonic and 5 anticyclonic is in contrast with the findings by Woodgate et al (2001), who reported a larger amount of anticyclonic eddies compared to cyclonic eddies at the Lomonosov Ridge, as well as Zhao et al (2014), who found anticyclonic predominance for halocline eddies in the deep EB. We cannot explain this difference in ratios between cyclonic and anticyclonic eddies at the EB slope and in the deep Eurasian and Canadian basins.…”
Section: Eddy Polarization 25contrasting
confidence: 99%
“…The warming and freshening trend in the Pacific-water layer has already been reported by many studies [e.g., Proshutinsky et al, 2009;Jackson et al, 2010;Giles et al, 2012;Timmermans et al, 2014]. The cooling trend in the central Canada basin and the warming trend along its southern perimeter is a consequence of deepening of the warm Atlantic Water in the central basin and concurrent upwelling of warm Atlantic Water at the boundaries, a manifestation of an intensification of the anticyclonic Beaufort Gyre in recent years [e.g., McLaughlin et al, 2009;Karcher et al, 2012;Zhong and Zhao, 2014].…”
Section: Temporal Trendsupporting
confidence: 60%
“…The autocorrelation at zero (Fig. 12a, c) show smaller values (0.6 -0.7) in the upper 100 m depth range, indicating active mesoscale processes (e.g., eddy activity observed in the Pacific-water layer [e.g., Zhao et al, 2014]). The zero-lag autocorrelations for spatial (Fig.…”
Section: Decorrelation Scalementioning
confidence: 99%
“…The zero-lag autocorrelations (Fig. 12a, c) show smaller values (0.6-0.7) in the upper 100 m depth range, indicating active mesoscale processes (e.g., eddy activity observed in the Pacific-water layer; e.g., Zhao et al, 2014). The zero-lag autocorrelations for spatial (Fig.…”
Section: Decorrelation Scalementioning
confidence: 94%
“…Note that the estimation of the autocorrelation quantifies basin-scale variability. Smaller-scale variability (e.g., mesoscale eddies on the deformation scale; Zhao et al, 2014) remains unresolved and is an intrinsic part of the autocorrelation function. The study area is the Amerasian Basin.…”
Section: Introductionmentioning
confidence: 99%